Does contingent pay encourage positive employee attitudes and intensify work?. (12th January 2017) - Ogbonnaya, Chidiebere; Daniels, Kevin; Nielsen, Karina
Abstract : This article explores the relationships between three dimensions of contingent pay – performance‐related pay, profit‐related pay and employee share‐ownership – and positive employee attitudes (job satisfaction, employee commitment and trust in management). The article also examines a conflicting argument that contingent pay may intensify work, and this can detract from its positive impact on employee attitudes. Of the three contingent pay dimensions, only performance‐related pay had direct positive relationships with all three employee attitudes. Profit‐related pay and employee share‐ownership had a mix of negative and no significant direct relationships with employee attitudes, but profit‐related pay showed U‐shaped curvilinear relationships with all three employee attitudes. The results also indicated that performance‐related pay is associated with work intensification, and this offsets some of its positive impact on employee attitudes.